DOES SUBSURFACE DRIP IRRIGATION IN SUGARCANE CULTIVARS IMPACT SOIL AGGREGATION? - Magalhães, Yasmin Reis [UNESP]; Coelho, Anderson Prates [UNESP]; Fernandes, Carolina [UNESP]; Dalri, Alexandre Barcellos [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
The aim was to evaluate the effect of subsurface drip irrigation with sugarcane cultivars, contrasting in the responsiveness to irrigation, in the aggregation of Oxisol clayey. The experiment was conducted in a clayey Oxisol (587g kg-1 of clay). Deformed soil samples were collected at twenty points in each four areas of sugarcane evaluated in the layers 0.00-0.10 m and 0.10-0.20 m. The areas corresponded to the irrigated and non-irrigated cultivation of cultivars CTC 4 and IACSP93-3046. The aggregate stability index, weighted average diameter of aggregates, physical fractionation of organic carbon and aggregate classes were determined and calculated. The data were submitted to the descriptive and multivariate factor statistics. According to the correlations of the variables, soil aggregation was divided into two processes, the first being called “Aggregates dimension” and the second “Aggregates stability.” It was observed that subsurface drip irrigation promotes greater soil “Aggregate stability” in areas cultivated with sugarcane. Additionally, sugarcane cultivars provide differences in soil aggregation, and the cultivar responsive to irrigation IACSP93-3046 promotes a larger soil “Aggregates dimension” than the non-responsive cultivar CTC 4.
IRRIGAÇÃO POR GOTEJAMENTO SUBSUPERFICIAL EM CULTIVARES DE CANA-DE-AÇÚCAR IMPACTAM A AGREGAÇÃO DO SOLO?
Keywords: Aggregate stability; Organic carbon; Oxisol; Weighted average diameter of aggregates